Hormone replacement therapy after prophylactic risk-reducing salpingo-oophorectomy and breast cancer risk in BRCA1 and BRCA2 mutation carriers: A meta-analysis. (December 2018) - Marchetti, C.; De Felice, F.; Boccia, S.; Sassu, C.; Di Donato, V.; Perniola, G.; Palaia, I.; Monti, M.; Muzii, L.; Tombolini, V.; Benedetti Panici, P.
Highlights: The safety of hormone replacement therapy (HRT) in BRCA mutation carriers is still debated. HRT after risk-reducing salpingo-oophorectomy (RRSO) should be weighed against the possible increased breast cancer risk. This is the first meta-analysis available in literature performed to clarify this clinical issue. This meta-analysis suggests that HRT after RRSO does not affect breast cancer risk in BRCA mutation carriers. Abstract: Background: Hormone replacement therapy (HRT) has been tested in women with BRCA1 and BRCA2 mutations who underwent risk-reducing salpingo-oophorectomy (RRSO), but its effect on breast cancer (BC) risk has never been appraised using meta-analysis comparison. We performed the first meta-analysis aimed to clarify whether HRT after RRSO could negatively impact on BC risk in women carriers of BRCA1 and BRCA2 mutations. Methods and material: Pubmed and Scopus databases were searched to retrieve articles written in the English language. Trials comparing RRSO with or without HRT were identified and only those trials with available BC events were included. BC risk was the main endpoint. Results: Three trials with 1100 patients were included. There was not a significantly higher BC risk in BRCA1 and BRCA2 mutation carriers receiving HRT after RRSO (HR = 0.98; 95% CI 0.63–1.52). There was a slightly but not significantly, benefit in BC risk reduction in favor of estrogen alone HRT versus estrogen plus progesterone HRT formulation (OR = 0.53; 95% CI 0.25–1.15). Conclusion: HRT use after RRSO in BRCA 1 and BRCA2 mutation carries does not affect BC risk. Comparison of the different HRT types suggests that estrogen alone should be related to lowest BC risk.